Functional Liver Imaging in Radiotherapy for Liver Cancer: A Systematic Review and Meta-Analysis - Zhou, Pi-Xiao; Zhang, Ying; Zhang, Quan-Bin; Zhang, Guo-Qian; Yu, Hui; Zhang, Shu-Xu (Frontiers in Oncology, 2022)
Backgrounds: Functional liver imaging can identify functional liver distribution heterogeneity and integrate it into radiotherapy planning. The feasibility and clinical benefit of functional liver-sparing radiotherapy planning are currently unknown. Methods: A comprehensive search of several primary databases was performed to identify studies that met the inclusion criteria. The primary objective of this study was to evaluate the dosimetric and clinical benefits of functional liver-sparing planning radiotherapy. Secondary objectives were to assess the ability of functional imaging to predict the risk of radiation-induced liver toxicity (RILT), and the dose-response relationship after radiotherapy. Results: A total of 20 publications were enrolled in descriptive tables and meta-analysis. The meta-analysis found that mean functional liver dose (f-MLD) was reduced by 1.0 Gy [95%CI: (-0.13, 2.13)], standard mean differences (SMD) of functional liver volume receiving ≥20 Gy (fV20) decreased by 0.25 [95%CI: (-0.14, 0.65)] when planning was optimized to sparing functional liver (P >0.05). Seven clinical prospective studies reported functional liver-sparing planning-guided radiotherapy leads to a low incidence of RILD, and the single rate meta-analysis showed that the RILD (defined as CTP score increase ≥2) incidence was 0.04 [95%CI: (0.00, 0.11), P <0.05]. Four studies showed that functional liver imaging had a higher value to predict RILT than conventional anatomical CT. Four studies established dose-response relationships in functional liver imaging after radiotherapy. Conclusion: Although functional imaging modalities and definitions are heterogeneous between studies, but incorporation into radiotherapy procedures for liver cancer patients may provide clinical benefits. Further validation in randomized clinical trials will be required in the future.